2017
DOI: 10.1007/s11695-017-2546-4
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric Roux-En-Y Gastric Bypass Surgery: Adipocyte Proteins Involved in Increased Bone Remodeling in Humans

Abstract: RYGB induced weight loss, and biochemical, hormonal, and body composition changes are associated with higher bone remodeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 57 publications
(78 reference statements)
0
9
2
Order By: Relevance
“…To our knowledge, most studies have measured body composition between 6 and 24 months after surgery. According to these studies, a biphasic loss of fat mass can be observed: an initial fast phase of fat mass reduction during the first year after surgery, that is followed by a second phase in which fat loss slows down until it reaches a point of maximum fat mass loss at month 24 20 . However, studies that have a longer follow-up period Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, most studies have measured body composition between 6 and 24 months after surgery. According to these studies, a biphasic loss of fat mass can be observed: an initial fast phase of fat mass reduction during the first year after surgery, that is followed by a second phase in which fat loss slows down until it reaches a point of maximum fat mass loss at month 24 20 . However, studies that have a longer follow-up period Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…These serum markers help to evaluate the degree of bone resorption versus bone formation after bariatric surgery and assist to determine the types of changes in bone turnover that lead to bone loss. For RYGB, numerous clinical studies showed major increases in bone resorption markers such as CTX and TRACP 5b, but only small increases in bone formation markers P1NP and OC ( Obinwanne et al, 2014 ; Casagrande et al, 2012 ; Shanbhogue et al, 2017 ; Yu et al, 2015 ; Muschitz et al, 2015 ; Bredella et al, 2017 ; Elias et al, 2014 ; Yu et al, 2016b ; Ivaska et al, 2017 ; Stein et al, 2013 ; von Mach et al, 2004 ; Coates et al, 2004 ; Riedt et al, 2006 ; Riedl et al, 2008 ; Fleischer et al, 2008 ; Carlin et al, 2009 ; Bruno et al, 2010 ; Yu et al, 2014 ; Sinha et al, 2011 ; Yu, 2014 ; Biagioni et al, 2017 ; Hofsø et al, 2016 ). After SG, an increase in resorption markers has also been noticed, however this was less pronounced than after RYGB ( Muschitz et al, 2015 ; Bredella et al, 2017 ; Ivaska et al, 2017 ; Stein et al, 2013 ; Schollenberger et al, 2015 ).…”
Section: Bone Loss After Bariatric Surgery: Resorption Versus Formatimentioning
confidence: 99%
“…Consistent herewith, vitamin D 3 deficiency is associated with low leptin levels ( Wagner et al, 2017 ). After SG and RYGB, serum leptin levels decrease due to loss of adipose tissue ( Shanbhogue et al, 2017 ; Biagioni et al, 2017 ; Grethen et al, 2012 ), whereas adiponectin levels increase ( Shanbhogue et al, 2017 ; Carrasco et al, 2014 ; Biagioni et al, 2017 ; Grethen et al, 2012 ; Carrasco et al, 2009 ). BMD was decreased in the limited number of studies in which BMD and adipokines were measured together ( Shanbhogue et al, 2017 ; Carrasco et al, 2014 ; Carrasco et al, 2009 ).…”
Section: Potential Mechanisms Underlying Bone Loss After Bariatric Sumentioning
confidence: 99%
“… AGB: adjustable gastric banding; VGB: Vertical Gastric Banding; RYGB: Roux-en-Y gastric bypass; SG: sleeve gastrectomy; BPD: biliopancreatic diversion; AgRP: agouti-related protein; α-MSH: alpha-melanocyte-stimulating hormone; CART: cocaine and amphetamine-regulated transcript; MCH: melatonin-concentrating hormone; NPY: neuropeptide Y; POMC: pro-opiomelanocortin; PP: polipeptide pancreatic; CCK: cholecystokinin; GIP: glucose-dependent insulinotropic polypeptide; GLP-1: glucagon-like peptide 1; GLP-2: glucagon-like peptide 2; OXM: oxyntomodulin; PYY: peptide YY; ↑: postsurgical increase; ↓: postsurgical decrease; ↔: no significant postsurgical change; T1: until 30-day follow up; T2: 3-month follow up T3: 6-month follow up; T4: 12-month follow up; T5: ≥24-month follow up. a Observational clinical studies only; b randomized clinical trials and observational clinical studies. 1 Netto et al (2016); 2 Tam et al (2016); 3 Urbanavicius et al (2013); 4 Bradley et al (2012); 5 Hansen et al (2011); 6 Netto et al (2015); 7 Chen et al (2012); 8 Illán-Gomez et al (2012); 9 Carrasco et al (2014); 10 Woelnerhanssen et al (2011); 11 Biagioni et al (2017); 12 Hoffstead et al (2017); 13 Garrido-Sanchéz et al (2012); 14 Palikhe et al (2014); 15 Haluzíková et al (2013); 16 Alam et al (2012); 17 Krieger et al (2012); 18 Jacobsen et al (2012); 19 Lips et al (2013); 20 Alamuddin et al (2017); 21 Ramón et al (2012); 22 Falkén et al (2011); 23 Nannipieri et al (2013); 24 Usinger et al (2011); 25 Umeda et al (2011); 26 Dirksen et al (2013); 27 Tsoli et al (2013); 28 Jorgensen et al (2012); 29 Rigamonti et al (2017); 30 Papamargaritis et al (2013); 31 Mallipedhi et al (2014); 32 Basso et al (2011); 33 Dixon et al (2011); 34 Peterli et al (2012); 35 Romero et al (2012); 36 Evans et al (201...…”
Section: Mechanisms Of Action and Resetting Energy Balance Following mentioning
confidence: 99%
“… 1 Netto et al (2016); 2 Tam et al (2016); 3 Urbanavicius et al (2013); 4 Bradley et al (2012); 5 Hansen et al (2011); 6 Netto et al (2015); 7 Chen et al (2012); 8 Illán-Gomez et al (2012); 9 Carrasco et al (2014); 10 Woelnerhanssen et al (2011); 11 Biagioni et al (2017); 12 Hoffstead et al (2017); 13 Garrido-Sanchéz et al (2012); 14 Palikhe et al (2014); 15 Haluzíková et al (2013); 16 Alam et al (2012); 17 Krieger et al (2012); 18 Jacobsen et al (2012); 19 Lips et al (2013); 20 Alamuddin et al (2017); 21 Ramón et al (2012); 22 Falkén et al (2011); 23 Nannipieri et al (2013); 24 Usinger et al (2011); 25 Umeda et al (2011); 26 Dirksen et al (2013); 27 Tsoli et al (2013); 28 Jorgensen et al (2012); 29 Rigamonti et al (2017); 30 Papamargaritis et al (2013); 31 Mallipedhi et al (2014); 32 Basso et al (2011); 33 Dixon et al (2011); 34 Peterli et al (2012); 35 Romero et al (2012); 36 Evans et al (2012); 37 Yousseif et al (2014); 38 Cazzo et al (2017); 39 Malin et al (2014); 40 Gelisgen et al (2012); 41 Barazzonni et al (2013); 42 Dar et al (2012). …”
Section: Mechanisms Of Action and Resetting Energy Balance Following mentioning
confidence: 99%